Transforming climate finance and green investment with blockchains - Marke, Alastair (Academic Press, an imprint of Elsevier, 2018)
Transforming climate finance and green investment with blockchains establishes and analyzes the connection between this new technology and global efforts to combat climate change. Realizing the benefits of blockchain can only come through a variety of alterations: the adoption of smart contracts, for instance, changes in governance and regulatory structures, and global agreements on privacy issues. Each chapter contains a "problem statement" that describes the challenges blockchain technology can address. The first book of its kind, Transforming climate finance and green investment with blockchains brings together original insights and opinions from experienced practitioners on a diverse range of practically relevant issues, helping readers understand blockchain technology and how it can accelerate the green economy.